A Pragmatics Analysis Of Promising Utterances In Barack Obama Speeches - Suwandi, Niken Wardiani; , Agus Wijayanto, Ph.D; , Dra. Dwi Haryanti, M.Hum (2013)
The study aims to describe the pragmalinguistics forms of promising utterances in Barack Obama speeches and to investigate illocutionary acts of promising utterances in Barack Obama speeches.The object of this study is promising utterance in five speeches of Barack Obama. This research belongs to qualitative research.In analyzing the promising utterance, the researcher: described the pragmalinguistics forms of promising utterance; identified and discussed illocutionary acts of promising utterance and drow conclusion and suggestion based on the analysis. As for the pragmalinguistic forms of promising utterances, the researcher found 36 data of constantive form (the percentage is 92%) and 3 data of pervormative form of promising utterance(the precentage is 8%). According the intention of the speakers, the researcher finds the intention such as reconfirming (the percentage is 3%), influencing (the percentage is 3%), offering (the percentage is 5%), assuring (the percentage is 43%) and affirming (the percentage is 46%).